Organizational Capacity and Profit Shifting - Katarzyna Anna Bilicka; Daniela Scur (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the effect of a firm's organizational capacity on the reported profitability of multinational enterprises (MNEs). Better organizational practices improve productivity and the potential taxable profits of firms. However, higher adoption of these practices may also enable more efficient allocation of profits across tax jurisdictions, lowering actual taxable profits. We present new evidence that MNE subsidiaries with better such practices, when located in high-tax countries, report significantly lower profits and have a higher incidence of bunching around zero returns on assets. We show these results are driven by patterns consistent with profit-shifting behavior. Further, using an event study design, we find that firms with better practices are more responsive to corporate tax rate changes. Our results suggest organizational capacity, especially monitoring-related practices, enables firms to engage in shifting profits away from their high-tax subsidiaries.
Keywords: H26; H32; M11; M20; 330; profit shifting; organizational capacity; monitoring practices; multinational firms